Empirical validation of marginalisation thesis on the participation in the informal economy in Goa - Manerkar, Gouri Kanta; Chandran, BP Sarath (Asian Economic and Financial Review, 2024)
This paper investigates the global increase in informal labor, focusing on two primary theoretical perspectives: the marginalization thesis and the reinforcement thesis. Previous empirical studies across various contexts have not definitively settled this debate. The current study, conducted in Goa, India, offers distinctive insights. Data from 200 informally employed individuals in both the formal and informal sectors was collected using snowball sampling. The findings of the binary logistic regression model reveal that the marginalisation thesis holds true, as individuals who are marginalised in terms of gender, age, education, and household employment in the informal sector are more likely to engage in informal employment. Conversely, the reinforcement thesis is supported when workplace characteristics such as flexible work timing and employment in construction services are considered. Therefore, the study concludes that a combination of marginalisation and reinforcement factors explains the reasons behind participation in the informal economy. Therefore, analysing labour market dynamics can offer valuable insights into informal employment.